2021
DOI: 10.3390/ncrna7030054
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in COVID-19: Emerging Insights and Current Questions

Abstract: The highly infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged as the causative agent of coronavirus disease 2019 (COVID-19) in late 2019, igniting an unprecedented pandemic. A mechanistic picture characterising the acute immunopathological disease in severe COVID-19 is developing. Non-coding RNAs (ncRNAs) constitute the transcribed but un-translated portion of the genome and, until recent decades, have been undiscovered or overlooked. A growing body of research continues to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 102 publications
1
16
0
Order By: Relevance
“…Despite their proven value as mechanism-based clinical stratification indicators, miRNAs have only started being explored in the context of COVID-19. It has been proposed that miRNAs might be involved in controlling inflammation during COVID-19 (Aslani et al, 2021;Gasparello et al, 2021;Houshmandfar et al, 2021;Matarese et al, 2020;Plowman and Lagos, 2021). Theoretical CC/miRNA regulatory networks have been proposed but not validated (Khokhar et al, 2022), whereas the potential of miRNA-like therapeutics has also been suggested (Ahn et al, 2021;Dash et al, 2021;Hum et al, 2021;Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their proven value as mechanism-based clinical stratification indicators, miRNAs have only started being explored in the context of COVID-19. It has been proposed that miRNAs might be involved in controlling inflammation during COVID-19 (Aslani et al, 2021;Gasparello et al, 2021;Houshmandfar et al, 2021;Matarese et al, 2020;Plowman and Lagos, 2021). Theoretical CC/miRNA regulatory networks have been proposed but not validated (Khokhar et al, 2022), whereas the potential of miRNA-like therapeutics has also been suggested (Ahn et al, 2021;Dash et al, 2021;Hum et al, 2021;Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, approximately 10 RNA-based therapeutics are approved by the FDA and multiple small RNA therapeutic approaches are in stages of clinical investigation for complex CNS and rare genetic disorders [ 17 , 225 ]. Importantly, we and others have discussed on the scope of ncRNA-based therapeutic applications in diseases such as COVID-19-induced neurological disorders, systemic inflammation and cardiovascular diseases [ 6 , 230 , 236–240 ]. As an example, in 2018, the FDA approved ‘Patisiran’- the first therapy based on administration of RNAi (siRNA-based) for the treatment of rare progressive polyneuropathy caused by hereditary transthyretin-mediated amyloidosis.…”
Section: Bioengineering Of Ncrnas For Neurological Diseasesmentioning
confidence: 99%
“…Despite their proven value as mechanism-based clinical stratification indicators, miRNAs have only started being explored in the context of COVID-19. It has been proposed that miRNAs might be involved in controlling inflammation during COVID-19 (Aslani et al, 2021;Gasparello et al, 2021;Houshmandfar et al, 2021;Matarese et al, 2020;Plowman and Lagos, 2021). Theoretical CC/miRNA regulatory networks have been proposed but not validated (Khokhar et al, 2022), whereas the potential of miRNA-like therapeutics has also been suggested (Ahn et al, 2021;Dash et al, 2021;Hum et al, 2021;Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%